The Relevance of the Concept Al-Amr bi al-Ma’ruf wa al-Nahy ‘an al-Munkar of Mu’tazilah in the Context of Islamic Preaching in Indonesia - Siraj, Fuad Mahbub; Arif, Ridwan (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This article is aimed at elaborating the relevance of the al-amr bi al-ma'rûf wa al-nahy 'an al-munkar concept of Mu’tazilah in the context of Islamic preaching in Indonesia. This research is a library research using a historical approach to obtain data and conducting content analysis. This research shows that Al-amr bi al-ma'rûf wa al-nahy 'an al-munkar is the actualization of faith manifested in a system of believer activity in the field of sociology and practiced regularly to influence the way of feeling, thinking, and acting either in the context of individual or socio-cultural. The influential sect of theology in Islamic history very actively carrying out al-amr bi al-ma’rûf wa al-nahy ‘an al-munkar is, among others, Mu’tazilah. In their perspective, the preaching is al-amr bi al-ma’rûf wa al-nahy ‘an al-munkar, meaning the command to do good things and the prohibition to do the evil. Mu’tazilah view that this concept is the fifth pillar of the struggle of life; in other words, al-amr bi al-ma’rûf wa al-nahy ‘an al -munkar must be actively confronted, and the more important point is its preaching rather than its contention. The significance of Mu’tazilah preaching has positive implications to the future development of Islam.